The Phytochemical constituents and biological activities of sungkai (Peronema canescens Jack) leaves hydroethanolic extracts - Rahayu, Ika; Sudrajat, Susana Elya; Sancnia, Sancnia; Puspasari, Monica; Timotius, Kris Herawan (JPBIO (Jurnal Pendidikan Biologi), 2024)
Peronema canescens, Jack commonly known as "sungkai," has been traditionally used as a herbal medicine for various health conditions. This study aimed to explore the bioactive compound of the P. canescens leaves hydroethanolic extract, along with assessing its antioxidant and antimutagenic properties. Liquid chromatography-mass spectrometry (LC-MS) was utilized for phytochemical analysis of the hydroethanolic extracts, while antioxidant activity was evaluated through the DPPH radical scavenging method. Quantification of total phenolic and flavonoid content was achieved via colorimetric analysis. Furthermore, the DNA protection activity was assessed using plasmid pBR322 subjected to free radical treatment. The primary bioactive compounds identified in the P. canescens hydroethanolic extracts belonged to the alkaloid and flavonoid groups. The antioxidant activity of P.canescens leaves hydroethanolic extracts showed an IC50 value of 0.02±0.00 µg/mL. Additionally, the total flavonoid and phenolic content were measured at 33,769±3,626 µg QE/mL and 638,924±6,683 µg GAE/mL, respectively. Notably, P.canescens exhibited significant potential in mitigating DNA damage. In conclusion, the P. canescens leaves hydroethanolic extracts demonstrate promising attributes as a herbal medicine, highlighting notable antioxidant and antimutagenic effects.